2020
DOI: 10.31289/biolink.v7i1.2856
|View full text |Cite
|
Sign up to set email alerts
|

UTILIZATION OF PAPAYA LEAVES (Carica papaya L.) TO CONTROL ONION PEST SPODOPTERA EXIGUA (LEPIDOPTERA: NOCTUIDAE)LEPIDOPTERA (NOCTUIDAE)

Abstract: Spodoptera exigua is a migrant pest that attacks onions simultaneously in groups. The utilization of papaya leaves to control pests due to papaya leaves have toxic compounds that can kill pests. This study aims to measure the ability of papaya leaves to control S. exigua larvae. This research was conducted using a completely randomized design (CRD) experimental method with two treatment factors. The first factor was papaya leaf concentration (0 g / l, 30 g / l, 70 g / l, 100 g / l, 120 g / l), and the second f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Hal ini didasarkan pada penelitian sebelumnya, dimana ekstrak daun papaya dapat membunuh kutu daun Aphis gossypii Glover pada terung (Ramadhona et al,2018) dan tomat (Sunarti, 2019). Selain itu, daun papaya juga dapat membunuh ulat bawang/hama larva penggerek daun (Spodoptera exigua) yang mengganggu tanaman bawang (Permadi et al,2020). Daun sirih (Piper bettle) dapat mengendalikan hama ulat tritip (Plutella xylostella) (Tumonglo et al,2017) dan membunuh lalat rumah (Daswito et al, 2019).…”
Section: Pendahuluanunclassified
“…Hal ini didasarkan pada penelitian sebelumnya, dimana ekstrak daun papaya dapat membunuh kutu daun Aphis gossypii Glover pada terung (Ramadhona et al,2018) dan tomat (Sunarti, 2019). Selain itu, daun papaya juga dapat membunuh ulat bawang/hama larva penggerek daun (Spodoptera exigua) yang mengganggu tanaman bawang (Permadi et al,2020). Daun sirih (Piper bettle) dapat mengendalikan hama ulat tritip (Plutella xylostella) (Tumonglo et al,2017) dan membunuh lalat rumah (Daswito et al, 2019).…”
Section: Pendahuluanunclassified
“…Commonly management pest technique used mechanical technique, nylon nets and light traps believes control S. exigua. Beside the technique, another study reported S. exigua can control in many way using microbe [12]; plant extract [13,14]; insect trap [15,16,17]; predator and parasitoid [17,18]. Application of chemical insecticide still allowed if insect pest population outbreak, typical selective, narrow spectrum and used the chemical compound in the limited number [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is minor, the papaya seeds have been studied for their antidiabetic activity [19]. In non-food and non-medicine applications, papaya leaves are also used as a bioherbicides [20], ectoparasite controls [21], and larvicides [22], as well in the control of the onion pest Spodoptera exigua [23].…”
Section: Introductionmentioning
confidence: 99%